Identification Of Chatbot Usage In Online Store Services Using Natural Language Processing Methods - Daud, Anshar; Irwanto, Dola; Said, Muh; Mubyl, Mutiarini; Mustamin, Mustamin (Advance Sustainable Science, Engineering and Technology, 2024)
Chatbot is one of the implementations of artificial intelligence in helping human tasks. The way the chatbot itself works is to answer questions directly according to the database that has been created. Chatbot helps online store owners answer questions from the same customers so that there is efficiency in terms of employee salaries. 40 questions that are often asked by customers to the online store admin. In its use, chatbot is one of the implementations of machine learning, where the function of machine learning itself is to improve the ability of machines to learn new information from data and develop the ability of machines to solve problems. Machine learning requires instruction from training data or input to teach machines how to solve problems, answer questions, and draw conclusions from the results of data processing. Furthermore, it is processed using Natural Language Processing (NLP). Natural Language Processing (NLP) is a branch of artificial intelligence that is able to study communication between humans and computers through natural language. The processing stages are identifying the intent, processing the input and displaying the results according to the input. Followed by testing the accuracy level. Then conduct testing using 40 question and answer data. Then obtained 36 answers that are appropriate and 4 answers that are not appropriate with the percentage of accuracy of the answers generated from the chatbot is 90 percent. The results of this test can answer the questions asked by customers. This chatbot can make it easier for customers to get information with a very good level of accuracy.